The Effect of Employees’ Commitment and Training to Work Performance in The University of Budi Luhur, Jakarta - Eti Ariyanti; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (International Journal of Education, Information Technology, and Others, 2022)
The aim of this research is to determind the effect of employees’ commintment and training to employees’ work performance in University of Budi Luhur, Jakarta either partial or simulatanious. Methodology applied to this research is quantitative with associative approach. Simple random sampling used to gather 70 respondents. Data analysis technique using validity test, reliability test, normality test, multicolineratiry test, linier regration test, multiple linier test, cooficient correlation test, determination coeficien test, tvalue and Fvalue. The research partially showed work commintment has a significant result to the employees’ productivity. This can be seen in a regetion formula Y = 17,894 + 0,551 X1. This hypothesis is supported by calculation of tvalue > ttable (3,855 > 1,995) and this is shown in ρ value < Sig.0,05 or significant value < 0,05 (0,000 < 0,05). The result of this research showed a significant effect to employees’ work performance in University of Budi Luhur, Jakarta in value of < 0,05 (0,000 < 0,05). Coeficient determination from comminetment variable and training show the result of 49,1% in University of Budi Luhur, Jakarta. So that H0 is rejected and H3 is accepted this means that the variables simultantly have significant result amongst work commitment (X1), training (X2), and work performance (Y).